Modifikasi field ball mampu meningkatkan motivasi belajar permainan bola besar pada siswa kelas X.1 SMA N 1 Sentani tahun ajaran 2012/2013 - Sudirman Sudirman (University of Cenderawasih, 2013)
Abstrack: fieldball modification can increase learn motivation games with big ball at studies X class SMAN 1 Sentani. Purpose this research is to find out of learn motivation student to standart competition as games with big ball. This research is action class research with two cycles.Research result : after student following process learning by modification field ball, were knew before process learning , more from student fill be afraid, keeping cool, falt slack following learning psycal education, have increase learn motivation changes to brave, energetic, and active to learning psycal education.Conclusion : increase learn motivation from before done modification, knew avarage learn motivation 2,69, and after modification field ball increase to 2,90, and in cycles cnd increase 3,35, so field ball modification be certain can increase learn motivation to student. Keyword : Modification, field ball, games with big ball